Psychological Factors Affecting Speaking Performance of EFL Students at Tadulako University - Maharani, Astrid Deswita; Kamaruddin, Abdul; Sadilia, Sukmawati; Said, Mawardin M. (Journal of English Language and Education, 2025)
This research aimed to identify and describe the psychological factors affecting the speaking performance of third-semester students of the English Education Study Program at Tadulako University. The study employed a quantitative descriptive design using a survey method with 100 randomly selected respondents. The instruments used were adapted from standardized scales: the Foreign Language Classroom Anxiety Scale, the Speaking Self-Efficacy Scale, and the Attitude/Motivation Test Battery. Data were analyzed using descriptive statistics through SPSS version 25, focusing on frequencies, percentages, and mean scores. The results revealed that students experienced a high level of anxiety (M = 3.13) and low self-confidence (M = 2.03), both of which served as psychological barriers in speaking English. Conversely, students demonstrated high motivation (M = 3.53) and positive attitudes (M = 3.59) toward English-speaking activities, which acted as psychological strengths enhancing engagement and persistence in learning. Overall, these findings suggest that emotional and motivational factors significantly influence students’ speaking performance. Therefore, it is recommended that lecturers foster a supportive learning environment that reduces anxiety, enhances confidence, and maintains students’ motivation and positive attitudes toward English learning.